ANALISIS LAPORAN KEUANGAN USAHA WARUNG SEMBAKO “ZAINUDDIN” - Diana Widhi Rachmawati; Hendri Gunawan; Antiarni Laras Nawang Sari (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2019)
Small and Medium Enterprises (SMEs) are one of the important components in the economic development of developing countries. UKM is very helpful for the country in supporting the economy. Financial Report Analysis is a tool and technique used in analyzing financial statements that have general objectives related to data and related to resources to generate estimates and benefits in business analysis. The related Financial Statement Analysis is also used in this study to discuss the method of ratio analysis, break event point analysis., cpmmon size analysis and trend analysis. Researchers in this case use quantitative research methods, sampling is done randomly, besides that it also uses research instruments as a tool for collecting data, while analyzing quantitative statistical data with the aim of testing the predetermined hypotheses. The sample from this study is Warung Sembako Zainuddi Zainudin is still being acquired is not good, because it is estimated that there is no doubt from the ratio analysis there are still numbers needed for improvement, the efforts carried out in accordance with the business. Achievement of the final results obtained from this study is small and is still in the process of development, therefore the business carried out by small and medium traders do with traditional offers, namely by word of mouth and waiting for buyers to come hope for overall guidance towards small businesses and it is from related parties, such as: Ministry of Cooperatives and Small and Medium Enterprises